Neurological complications of arterial hypertension. Issue 12 (December 1982) - Trompeter, R S; Smith, R L; Hoare, R D; Neville, B G; Chantler, C
Abstract : During a 10-year period 45 children were identified as having had neurological complications associated with severe arterial hypertension. Convulsions were the most common complication, occurring in 42 (82%) children. Two (4%) children each presented with a facial palsy and 2 (4%) with alterations in the level of consciousness. Nineteen (42%) presented with epileptic seizures as the first sign of arterial hypertension. The prognosis for children having had a single episode of hypertensive encephalopathy was good. Long-term follow-up showed no permanent neurological deficit on physical examination, and no focal abnormality on brain scan by computerised tomography. Psychometric analysis similarly failed to show any significant difference in cognitive assessment between children having had an episode of hypertensive encephalopathy and a control group with chronic renal disease, although reading skills were generally behind for chronological age and the average IQ was about 90 in both groups.